Twenty-first century tendencies: stage writing in europe vs. Film scriptwriting in Spain : (The question about the contemporary nature of spanish cinema) - Orosa, Miguel A.; Galarza-Ligña, Viviana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article aims to study the main patterns of contemporaneity in the field of stage writing, especially in Europe. Particular reference is made to the problem and function of the text in the age of the image and other issues of special relevance. These notes or stage patterns are compared with those of the most publicized current texts of cinema in Spain, giving rise to the debate on the adequacy of these cinematographic texts to the signs of contemporaneity. The aim of this study is to find out whether the mentioned film texts follow the current guidelines of European contemporary stage writing.